Shear performance of reinforced concrete (RC) beams strengthened with mortar-based composites under monotonic and fatigue loading - Liu, Xiangsheng (2025)
Reinforced concrete (RC) beams form the backbone of modern structures, yet their performance is increasingly compromised by aging, environmental degradation, outdated design standards, unauthorised modifications, increased load demands, impact damage, poor construction quality, and corrosion. These challenges have significantly heightened the demand for effective structural maintenance and strengthening strategies. While fibre-reinforced polymers (FRPs) are widely adopted due to their high strength-to-weight ratio and design flexibility, their limitations—such as poor fire resistance, environmental toxicity, and incompatibility with concrete substrates—restrict their applicability. In this context, mortar-based composites, including Steel-Reinforced Grout (SRG) and High-Performance Fibre-Reinforced Concrete (HPFRC), have emerged as promising alternatives for enhancing the shear capacity of RC beams. Despite their potential, research on SRG and HPFRC systems remains limited, particularly under cyclic and fatigue loading conditions.